Metal-doped porous carbon, silicon-carbon material and preparation method thereof

By doping lithium in porous carbon and combining nano-silicon deposition and solid electrolyte thin film deposition, silicon carbon materials with core-shell structures are formed, and the existing silicon carbon materials have been solved, with the problems of low rate performance, large expansion rate and poor circulation performance, and the performance improvement of high-energy-density lithium-ion batteries has been achieved.

CN118419892BActive Publication Date: 2025-04-08CNBM ZHEJIANG MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410454161.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-16
Publication Date
2025-04-08
Estimated Expiration
2044-04-16

AI Technical Summary

Technical Problem

Existing silicon carbon materials have problems such as low rate performance, large expansion rate and poor circulation performance in lithium-ion batteries, which are difficult to meet the needs of high-energy-density lithium-ion batteries.

Method used

By doping lithium in porous carbon, the electron conductivity of the material is enhanced, and the porous carbon structure is modified by alkaline gas to form a silicon carbon material with a core-shell structure.

Benefits of technology

It significantly improves the rate performance and circulation performance of silicon-carbon materials, reduces the expansion rate, improves the stability and conductivity of the material, and enhances the high-temperature storage performance and liquid retention performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118419892B_ABST
    Figure CN118419892B_ABST
Patent Text Reader

Abstract

The present invention discloses metal-doped porous carbon, silicon-carbon materials and preparation methods thereof. A carbon-based precursor, a pore-forming agent and lithium amine are added to an organic solvent for dispersion, drying and solidification to obtain a porous carbon precursor; an alkaline gas is introduced and high-temperature treatment is performed to obtain lithium-doped porous carbon; the porous carbon is transferred to a tubular furnace, the air in the tube is discharged, nano-silicon is deposited, and a solid electrolyte film is deposited on the surface by a deposition method to obtain a silicon-carbon composite material. The present invention improves the electronic conductivity and the first efficiency by doping lithium into the porous carbon; the amino resin is modified to improve the stability and electronic conductivity of the material and improve the cycle performance; a pore-forming agent is doped to improve the uniformity of the material pores and the size of the pore diameter, and reduce the expansion of silicon. A solid electrolyte is deposited on the outermost layer by a deposition method to avoid side reactions caused by the contact of the inner core nano-silicon with the air. The material has the characteristics of thin thickness and high density, and improves the first coulomb efficiency and its high-temperature storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and relates to silicon-carbon materials, and in particular to metal-doped porous carbon, a silicon-carbon material prepared from the metal-doped porous carbon, and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology, people have put forward higher requirements on the capacity and energy density of batteries, which requires the search for better negative electrode materials.

[0003] Compared with traditional carbon negative electrode materials, silicon as a negative electrode material has the following advantages:

[0004] 1. Large capacity: The theoretical specific capacity of silicon can reach 4200mAh / g, which is about 10 times that of carbon. Therefore, batteries made of silicon can store more electrical energy in the same volume, improving the working time and performance of the battery.

[0005] 2. High energy density. Compared with traditional materials such as graphite, silicon materials have higher energy density and can achieve longer battery life.

[0006] Mainstream silicon negative electrodes can be divided into two categories: silicon-oxygen negative electrodes and silicon-carbon negative electrodes. The main advantages of silicon-oxygen negative electrodes are high reversible capacity, cycle performance and rate performance; at the same time, they have been developed for a long time and have a relatively stable process route. Its main problem is that the first coulombic efficiency is too low. The silicon-carbon negative electrode has a higher gram capacity and a higher efficiency in the first charge and discharge; however, the coulombic efficiency and cycle efficiency of its electrode are still lower than those of carbon negative electrode materials. The main common defect of silicon negative electrodes is that the expansion rate is much greater than that of carbon negative electrodes. During the lithium insertion-delithiation process, defects in the silicon-containing crystal structure occur, which is an important reason why silicon negative electrodes must be mixed and doped with carbon negative electrodes or pre-treated.

[0007] Silicon-carbon materials are used in high-energy-density lithium-ion batteries and other fields due to their high specific capacity, wide material sources, large expansion, and poor electronic conductivity. At present, there are two types of commercial silicon-carbon materials, sand-milled silicon-carbon and silane cracking silicon-carbon. The sand-milled silicon-carbon materials have moderate specific capacity (1250mAh / g), large expansion when fully charged (300%), and poor cycle performance. Silane cracking silicon-carbon materials have high specific capacity (1800-1900mAh / g), small expansion when fully charged (90%), and good cycle performance. Porous carbon has good consistency in pore structure, relatively uniform pores, slightly larger pore size, and high strength, so that it can uniformly accommodate nano-silicon. Reducing expansion is considered the most important improvement of silane cracking silicon-carbon. However, due to the problems of poor electronic conductivity of porous carbon itself, it needs to be doped to improve the rate performance of the material. Summary of the invention

[0008] In order to improve the rate performance of silicon-carbon materials, reduce expansion and improve the consistency of materials, the present invention provides a metal-doped porous carbon, a silicon-carbon material and a preparation method thereof. The prepared lithium-doped porous carbon is deposited with nano-silicon in its core and a thin film on the surface to improve the rate performance and cycle performance of the material.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] The present invention first provides a metal-doped porous carbon, wherein the metal-doped porous carbon is lithium-doped porous carbon, wherein the content of lithium is 1wt%-5wt%.

[0011] In the present invention, a small amount of Li doping is beneficial to improving the first effect of the silicon-carbon negative electrode material and improving the electronic conductivity of the porous carbon, but excessive doping will lead to a decrease in the strength of the porous carbon.

[0012] The present invention further provides a silicon-carbon material, which has a core-shell structure, wherein the core is made of the lithium-doped porous carbon deposited nano-silicon and the shell is a film.

[0013] As a preferred solution of the present invention, the shell is a solid electrolyte film, and the mass of the shell accounts for 1wt%-10wt% based on 100% mass of the silicon-carbon material.

[0014] The present invention also provides a method for preparing the above silicon-carbon material, the preparation method comprising the following steps:

[0015] S1 Preparation of lithium-doped porous carbon: adding a carbon-based precursor, a pore-forming agent and lithium amide into an organic solvent, uniformly dispersing, spray drying, and curing at a certain temperature to obtain a porous carbon precursor; placing the porous carbon precursor in a tube furnace, heating it, and introducing alkaline gas to obtain lithium-doped porous carbon;

[0016] S2: preparing lithium silicon porous carbon material: placing the lithium-doped porous carbon obtained in step S1 in a tube furnace, introducing an inert gas to exhaust the air, heating, introducing a silane mixed gas to deposit nano-silicon, and obtaining a lithium silicon porous carbon material;

[0017] S3 depositing a thin film: depositing a thin film on the surface of the lithium silicon porous carbon material obtained in step S2 by a deposition method to obtain a silicon carbon composite material.

[0018] As a preferred embodiment of the present invention, in step S1, the mass ratio of the carbon-based precursor, the pore-forming agent, the lithium amide and the organic solvent is 100:1-5:1-5:500-1000; the carbon-based precursor is an amino resin, the pore-forming agent is one of polystyrene microspheres, polymethyl methacrylate or aminocarbamoyl hydrazide, and the organic solvent is one of acetone, methanol, ethyl acetate or butanone.

[0019] As a preferred embodiment of the present invention, in step S1, the curing temperature is 300°C-600°C, and the curing time is 1h-6h; the temperature is raised to 500°C-800°C, and an alkaline gas is introduced for 1h-6h at a flow rate of 50mL / min-200mL / min, and the alkaline gas is one of ammonia, phosphine or tetrahydrogen.

[0020] In the present invention, the alkaline gas can modify the carbon matrix during the carbonization process and dope N and P to improve the electronic conductivity of the porous carbon material.

[0021] As a preferred embodiment of the present invention, in step S2, the temperature is heated to 400°C-600°C, and a silane mixed gas is introduced. The silane mixed gas is a mixture of silane and argon with a volume ratio of 1-5:10, a flow rate of 50mL / min-500mL / min, and an introduction time of 30min-300min.

[0022] As a preferred solution of the present invention, in step S3, the deposition method is specifically one of magnetron sputtering, atomic vapor deposition or pulsed laser deposition.

[0023] As a preferred embodiment of the present invention, the solid electrolyte is Li 1.3 Al 0.3 Ti 1.7 (PO4)3,Li7La3Zr2O 12 or Li 0.35 La 0.55 One of TiO3.

[0024] Finally, the present invention provides application of the silicon-carbon material in lithium-ion batteries.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) The present invention improves the electronic conductivity of the material, improves the first coulomb efficiency, and reduces the defects of the material by doping lithium into the porous carbon; at the same time, the amino resin is modified by alkaline gas and a porous carbon structure is generated by high-temperature treatment, thereby improving the stability of the material and improving the cycle performance; a pore-forming agent is doped into the carbon-based precursor to improve the uniformity of the pores and the size of the pores during the carbonization process of the material, thereby reducing the expansion of silicon during the charge and discharge process.

[0027] 2) The present invention deposits a solid electrolyte on the outermost layer of the lithium silicon porous carbon material through a deposition method to avoid side reactions between the inner core nano-silicon and the air. At the same time, the solid electrolyte deposited by the deposition method has the characteristics of thin thickness and high density, which improves the initial efficiency and high-temperature storage performance of the silicon-carbon composite material, has high powder conductivity, improves the constant current ratio of the material, and has a high specific surface area, which improves the liquid retention performance of the material and improves the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a SEM image of the silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0029] In order to make the technical means, creative features, purpose and efficacy of the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without creative work all belong to the protection scope of the present invention. The experimental methods in the following embodiments, unless otherwise specified, are conventional methods, and the materials, reagents, etc. used in the following embodiments, unless otherwise specified, can all be obtained from commercial channels.

[0030] The present invention provides metal-doped porous carbon, silicon-carbon material and preparation method thereof. A carbon-based precursor, a pore-forming agent and lithium amide are added to an organic solvent and dispersed evenly, spray-dried and solidified to obtain a porous carbon precursor; an alkaline gas is introduced and high-temperature treatment is performed to obtain lithium-doped porous carbon; the lithium-doped porous carbon is transferred to a tubular furnace, an inert gas is introduced to exhaust the air in the tube, a silane mixed gas is introduced to perform nano-silicon deposition, and a layer of solid electrolyte film is deposited on the surface by a deposition method to obtain a silicon-carbon composite material.

[0031] The present invention improves the electronic conductivity of the material and the first coulomb efficiency by doping lithium in porous carbon; at the same time, by using alkaline gas to modify amino resin to generate a porous carbon structure, the stability of the material is improved and the cycle performance is improved; a pore-forming agent is doped in the carbon-based precursor to improve the uniformity of the pores and the size of the pores during the carbonization process of the material, and reduce the expansion of silicon during the charge and discharge process. Through the deposition method, a solid electrolyte is deposited on the outermost layer of the material to avoid side reactions caused by the contact of the inner core nanosilicon with the air. At the same time, the solid electrolyte deposited by the deposition method has the characteristics of thin thickness and high density, which improves the first efficiency of the silicon-carbon composite material and its high-temperature storage performance.

[0032] Example 1

[0033] This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0034] S1: 100 g of amino resin, 3 g of polystyrene microspheres and 3 g of lithium amide were added to 800 g of acetone organic solvent, dispersed evenly, spray dried, and cured at a temperature of 450 ° C for 3 h to obtain a porous carbon precursor; the porous carbon precursor was transferred to a tube furnace, heated to 600 ° C, and ammonia was introduced at a flow rate of 100 mL / min for 3 h to obtain lithium-doped porous carbon;

[0035] S2: The lithium-doped porous carbon was transferred to a tube furnace, argon inert gas was introduced to exhaust the air in the tube, and a silane mixed gas (volume ratio, silane: argon = 3:10) was introduced, and the temperature was heated to 500°C, the flow rate was 100 mL / min, and the introduction time was 120 min to perform nano-silicon deposition to obtain a lithium-silicon porous carbon material;

[0036] S3: A layer of Li is deposited on the surface of the lithium silicon porous carbon material by magnetron sputtering (magnetron sputtering is a commonly used method in this field and will not be described in detail). 1.3 Al 0.3 Ti 1.7 (PO4)3 film to obtain a silicon-carbon composite material.

[0037] Example 2

[0038] This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0039] S1: 100 g of amino resin, 1 g of polymethyl methacrylate and 1 g of lithium amide were added to 500 g of methanol organic solvent, dispersed evenly, spray dried, and cured at 300 ° C for 6 h to obtain a porous carbon precursor; the porous carbon precursor was transferred to a tube furnace, heated to 500 ° C, and phosphine gas was introduced at a flow rate of 200 mL / min for 6 h to obtain lithium-doped porous carbon;

[0040] S2: The lithium-doped porous carbon was transferred to a tube furnace, argon inert gas was introduced to exhaust the air in the tube, and then a silane mixed gas (volume ratio, silane: argon = 1:10) was introduced, and the temperature was heated to 400°C, the flow rate was 500 mL / min, and the introduction time was 30 min to perform nano-silicon deposition to obtain a lithium-silicon porous carbon material;

[0041] S3: A layer of Li7La3Zr2O is deposited on the surface of the lithium silicon porous carbon material by using a vapor deposition method (the vapor deposition method is a commonly used method in the prior art and will not be described in detail). 12 film to obtain a silicon-carbon composite material.

[0042] Example 3

[0043] This embodiment provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0044] S1: 100 g of amino resin, 5 g of carbamoyl hydrazide and 5 g of lithium amide were added to 1000 g of ethyl acetate organic solvent, dispersed evenly, spray dried, and cured at a temperature of 600° C. for 1 h to obtain a porous carbon precursor; the porous carbon precursor was transferred to a tube furnace, heated to 800° C., and tetrahydrogen dinitrogen gas was introduced at a flow rate of 50 mL / min for 6 h to obtain lithium-doped porous carbon;

[0045] S2: The lithium-doped porous carbon was transferred to a tube furnace, argon inert gas was introduced to exhaust the air in the tube, and then a silane mixed gas (volume ratio, silane: argon = 5:10) was introduced, and the temperature was heated to 600°C, the flow rate was 500mL / min, and the introduction time was 30min to perform nano-silicon deposition to obtain a lithium-silicon porous carbon material;

[0046] S3: A layer of Li is deposited on the surface of the lithium silicon porous carbon material by vapor deposition method (vapor deposition method is a commonly used method in the prior art and will not be described in detail). 0.35 La 0.55 TiO3 film to obtain a silicon-carbon composite material.

[0047] Comparative Example 1

[0048] The difference from Example 1 is that lithium amide is not added and ammonia gas is not introduced. The other steps are the same as Example 1.

[0049] Comparative Example 2

[0050] Different from Example 1, the solid electrolyte is not deposited by using a vapor phase deposition technique, but a liquid phase method is used to deposit amorphous carbon on the surface of the lithium silicon porous carbon material.

[0051] The preparation process of depositing amorphous carbon on the surface of lithium silicon porous carbon material by liquid phase method is as follows: 100g lithium doped porous carbon in step S2 of embodiment 1 and 5g Li 1.3 Al 0.3 Ti 1.7 (PO4)3, 1g of asphalt was added to xylene solvent, dispersed evenly, then spray dried, and carbonized at 1100℃ for 3h to obtain Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and amorphous carbon coated silicon-carbon composites.

[0052] SEM Testing

[0053] Figure 1 This is a SEM image of the silicon-carbon composite material prepared in Example 1. It can be seen from the image that the material has a granular structure with a particle size between 5-10 μm, and a layer of granular material is deposited on its surface.

[0054] Physical and chemical performance test:

[0055] The specific surface area and tap density of each silicon-carbon composite material were tested with reference to the national standard GB / T 38823-2020 "Silicon Carbon", and the conductivity of each composite material was tested using a four-probe tester. The pore size, pore volume and powder electronic conductivity of the silicon-carbon composite materials in Examples 1-3 and Comparative Examples 1-2 were also tested respectively; the test results are shown in Table 1 below.

[0056] Button cell battery test:

[0057] The silicon-carbon composite materials corresponding to Examples 1-3 and Comparative Examples 1-2 were used as negative electrode materials for lithium-ion batteries to prepare button batteries according to the following method:

[0058] A binder, a conductive agent and a solvent are added to each corresponding silicon-carbon composite material, stirred to make a slurry, coated on a copper foil, and dried and rolled to obtain a negative electrode sheet; the binder used is LA132, the conductive agent is SP (conductive carbon black), the solvent is NMP, and the usage ratio of the composite material, SP, LA132, and NMP is 95g:1g:4g:220mL; the electrolyte is a solution with LiPF6 as the electrolyte, and the concentration is 1mol / L, wherein the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film.

[0059] Each button cell was assembled in an argon-filled glove box, and then the electrochemical performance was tested. Specifically, the electrochemical performance was tested on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The test results are shown in Table 1 below.

[0060] The negative electrode sheet of the above button battery was also tested for full-charge expansion. The specific test process is: the thickness D1 of the negative electrode sheet of the rolled button battery was tested, and then the full-charge thickness D2 of the negative electrode sheet was dissected when the button battery was fully charged to 100% SOC, and then the expansion rate was calculated (expansion rate = (D1-D2) / D1*100%); the test results are shown in Table 1 below.

[0061] Table 1. Physical and chemical properties test results

[0062]

[0063]

[0064] It can be seen from the data in Table 1 that the specific capacity and the first efficiency of the silicon-carbon composite materials prepared in Examples 1-3 are significantly better than those in Comparative Examples 1-2. The reason is that by doping lithium into the porous carbon, the electronic conductivity of the material is improved and the defects of the material are reduced, the first efficiency and the powder conductivity are improved, and the solid electrolyte is deposited by the deposition method to reduce the defects of the material, further improving the first efficiency and conductivity of the material.

[0065] Soft pack performance test:

[0066] The composite materials corresponding to Examples 1-3 and Comparative Examples 1-2 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates) and positive electrode ternary materials (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2), electrolyte and diaphragm are assembled into a 5Ah soft-pack battery; wherein the diaphragm is celegard 2400, the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.3 mol / L) to prepare the soft-pack battery.

[0067] The following performance tests are performed on each soft pack battery:

[0068] a. Liquid absorption capacity test: Use a 1mL burette and absorb VmL of electrolyte, add a drop on the surface of each negative electrode, and time it until the electrolyte is completely absorbed. Record the time t and calculate the liquid absorption rate S=V / t of each negative electrode. The test results are shown in Table 2 below.

[0069] b. Liquid retention rate test: According to the parameters of each negative electrode sheet, calculate the theoretical liquid absorption m1 of the corresponding negative electrode sheet, and weigh the weight of the negative electrode sheet as m2. Then, place the negative electrode sheet in the electrolyte and soak it for 24 hours. Weigh the weight of the negative electrode sheet as m3, and calculate the liquid absorption of the negative electrode sheet as m3-m2, according to the following formula:

[0070] Liquid retention rate = (m3-m2)*100% / m1; the test results are shown in Table 2 below.

[0071] Table 2. Soft pack performance test results

[0072]

[0073]

[0074] It can be seen from Table 2 that the liquid absorption and retention capacity of the silicon-carbon composite materials provided by Examples 1-3 is higher than that of Comparative Examples 1-2; the reason may be that the silicon-carbon composite materials provided by the present invention have a larger specific surface area, which can directly improve the liquid absorption and retention capacity of the silicon-carbon composite materials.

[0075] c. Rate and cycle performance test:

[0076] Carrying out cycle performance test and rate test on each prepared soft-pack battery;

[0077] The test conditions for the cycle performance test are as follows: the charge and discharge voltage range is 2.5 to 4.2 V, the temperature is 25 ± 3.0 ° C, the charge and discharge rate is 1.0 C / 1.0 C, and the number of cycles is 500 times;

[0078] The test conditions of the rate test are: testing the constant current ratio of each soft-pack battery under 2C conditions; the test results are shown in Table 3 below.

[0079] Table 3. Rate and cycle performance test results

[0080]

[0081] It can be seen from Table 3 that the rate and cycle performance of the soft-pack lithium-ion battery prepared using the silicon-carbon composite material provided by Examples 1-3 are significantly better than those of Comparative Examples 1-2. The example material has a high powder conductivity, which improves the constant current ratio of the material; at the same time, the example material has a high specific surface area, which improves the liquid retention performance of the material and improves the cycle performance.

[0082] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A silicon-carbon material, characterized in that: The silicon-carbon material has a core-shell structure, the core is made of lithium-doped porous carbon deposited nano-silicon, and the shell is a thin film; the lithium-doped porous carbon, wherein the lithium content is 1-5wt%; The shell is a solid electrolyte film. Based on the mass of the silicon-carbon material being 100%, the mass of the shell accounts for 1wt%-10wt%; the solid electrolyte is Li 1.3 Al 0.3 Ti 1.7 (PO4)3,Li7La3Zr2O 12 or Li 0.35 La 0.55 One of TiO3; The preparation method of the silicon-carbon material comprises the following steps: S1 Preparation of lithium-doped porous carbon: adding a carbon-based precursor, a pore-forming agent and lithium amide to an organic solvent, uniformly dispersing, spray drying, and curing at a certain temperature to obtain a porous carbon precursor; placing the porous carbon precursor in a tube furnace, heating, and introducing alkaline gas to obtain lithium-doped porous carbon; the mass ratio of the carbon-based precursor, the pore-forming agent, lithium amide and the organic solvent is 100:1-5:1-5:500-1000; the carbon-based precursor is an amino resin, the pore-forming agent is one of polystyrene microspheres, polymethyl methacrylate or aminocarbamoyl hydrazide, and the organic solvent is one of acetone, methanol, ethyl acetate or butanone; the curing temperature is 300℃-600℃, and the curing time is 1h-6h; heating to 500℃-800℃, introducing alkaline gas for 1h-6h, with a flow rate of 50mL / min-200mL / min, and the alkaline gas is one of ammonia, phosphine or tetrahydrogen; S2: preparing lithium silicon porous carbon material: placing the lithium-doped porous carbon obtained in step S1 in a tube furnace, introducing an inert gas to exhaust the air, heating, introducing a silane mixed gas to deposit nano-silicon, and obtaining a lithium silicon porous carbon material; S3 depositing a thin film: depositing a thin film on the surface of the lithium silicon porous carbon material obtained in step S2 by a deposition method to obtain a silicon carbon composite material.

2. The silicon-carbon material according to claim 1, characterized in that: In step S2 of the preparation method, the temperature is heated to 400°C-600°C, and a silane mixed gas is introduced. The silane mixed gas is a mixture of silane and argon, with a volume ratio of 1-5:10, a flow rate of 50mL / min-500mL / min, and an introduction time of 30min-300min.

3. The silicon-carbon material according to claim 1, characterized in that: In step S3 of the preparation method, the deposition method is specifically one of magnetron sputtering, atomic vapor deposition or pulsed laser deposition.

4. An application of the silicon-carbon material as claimed in claim 1, characterized in that: Application of the silicon-carbon material in lithium-ion batteries.

Citation Information

Patent Citations

  • Nitrogen and lithium doped porous carbon and silicon carbon composite material and preparation method and application thereof

    CN117832447A